Novel corona virus diseases 2019 dan dampak yang timbul pada keluarga - Caturjuniandri, Myllani Tsesar (Peneleh Research Institute, 2020)
This study aims to explain that Covid-19 has quite an impact on individual psychology in terms of emotional changes, anxiety, and fear. The method used is a qualitative narrative type. Covid-19 does not only affect psychologically, but also changes the way individuals establish social relations with the community by maximizing the use of social media in accordance with government regulations related to pandemic prevention. Daily activities are also transformed due to the existence of covid prevention regulations. However, in reality there are still many people who do not comply with health protocols. Abstrak Penelitian ini bertujuan untuk menjelaskan bahwa covid-19 cukup berdampak pada psikologis individu dalam hal perubahan emosi, serta rasa cemas, dan takut. Metode yang digunakan ialah berjenis naratif kualitatif. Tak hanya memengaruhi psikologi, pandemi ini juga mengubah cara individu dalam menjalin hubungan sosial dengan masyarakat dengan pemaksimalan penggunaan sosial media sesuai dengan peraturan pemerintah terkait pencegahan pandemi. Aktivitas sehari-hari pun mengalami perubahan yang cukup berbeda akibat adanya peraturan pencegahan covid. Namun pada kenyataan masih banyak warga yang kurang patuh terhadap protokol kesehatan.